Pengelolaan Pendidikan Dalam Meningkatkan Mutu Kelompok Bermain Nur-Masithah Sampang Madura - Ach. Baidowi; Riza Aulia Widyaningsih (STAI Publisistik Thawalib Jakarta, 2022)
Management of education in an educational organization is very important to do to create a special educational atmosphere for effective, efficient and conducive learning so that educational goals can be easily achieved. The purpose of this research is to describe the management of education, namely the management of learning, classrooms, teachers and offices and to describe the impact of education management on the quality of education in KB Nur-Masithah Sampang. The research method is a case study approach. Data collection techniques with interviews, observation and documentation. Data analysis technique with reduction, data presentation and conclusion drawing. While the data validity technique is triangulation of sources and techniques. The results showed: the management of education in the aspect of learning management by setting the learning schedule into three parts, namely thematic, religion and sports and educational games. Aspects of classroom management by grouping the class into 2 parts, namely the age group of 3-4 years and the age group of 5-6 years. Aspects of teacher management by dividing teachers based on class groups. Aspects of office management by arranging the teacher's room and office. While the impact of education management on school quality is that learning runs and is efficient, principals can measure learning success and teachers can measure and control student achievement.